PEMANFAATAN PASSIVE SAMPLER UNTUK MONITORING KUALITAS NO2 DALAM UDARA AMBIEN DI BEBERAPA LOKASI DI INDONESIA - Susanto, Joko Prayitno (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2004)
Analysis methods by using passive sampler for the content of pollutant materials in the ambient air, such as the content of NO2, SO2, O3, etc, has been widely used and applied in several countries. The advantage of this method is easier to carry and more moveable, and taking samples among various locations with different weather, compares to others. In Indonesia this method is not much known yet.The writers through a collaboration of research with The University of Tokushima-Japan, is trying to apply one of passive sampler method in order to measure the concentration of NO2 in the air on several locations in Jakarta, Surabaya and Bandung. Hence, The result of analyze in Indonesian was comparing with the result in the others country by used thesame methods. The conclusion of this research is the quality of the air on Indonesian city worse than the Asia city, so in the future Indonesian government can give more attention to handle the air pollutant.